ECB Collateral Criteria: A Narrative Database 2001–2013 - Jakob Eberl; Christopher Weber (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
This paper offers an encompassing analysis of the ECB's collateral criteria between 2001 and 2013. A comprehensive database of changes to collateral criteria is compiled and structured by asset classes. The main findings can be summarized in three stylized facts: (1) Since the outbreak of the financial crisis, the ECB has been six times more active in collateral policy making than in the seven years before. Thereby, the ECBbroadened the eligible collateral pool both (2) at the extensive margin, increasing the quantity of eligible asset types by a factor of 36 and (3) at the intensive margin, by lowering and partially suspending the minimum credit rating requirements. This led toan additional increase in the number of eligible asset types by a factor of 110. The paper tracks these developments using a narrative approach.
Keywords: E58; F33; G01; H12; 330; European Central Bank; collateral; European debt crisis; reserve transaction; segmental pooling.